Hybrid Machine Learning Techniques to detect Real Time Human Activity using UCI Dataset - Arshad, Muhammad; Hassan Jaskani, Fawwad; Ayub Sabri, Muhammad; Ashraf, Fatima; Farhan, Muhammad; Sadiq, Maria; Raza, Hammad (EAI Endorsed Transactions on Internet of Things, 2021)
The cell phone is assuming a crucial job in present day life. It offers types of assistance and applications, for example, location tracking, medical applications, and human activity examination. All android smartphones have motion sensors i.e. Accelerometer, gyroscope, in order to detect motion of a user in a very precise way. In early conditions, committed sensors were utilized for activity acknowledgment. Different techniques are developed for distinguishing normal or human activities scenes in the crowd by processing the video or an image. A novel KNN-SVM human activity detection method is proposed to detect human activities in the UCI dataset for complex multi-process physical activities. Model trained with machine learning algorithms to capture the temporal dependency, normal sequences with high dimension is uniformly utilized to train the model to discriminate each activity. In the classification process, 2 different efficient classifiers are applied to identify the types of human activities in the UCI dataset. Support Vector Machine and K-Nearest Neighbour are applied in the proposed method for the classification. The efficiency of each classifiers is about 85% to 87%. The classification efficiency is comparable with existing literature after applying the majority decision in these classification techniques.
Keywords: Machine Learning; KNN; SVM; Human Activity Recognition